STAM-binding Protein-like 1 Promotes Growth and Migration of Colorectal Cancer by NF-ΚB Pathway - Zhou, Xinghua; Cheng, Yue; Kang, Jian; Mao, Gang (Protein and Peptide Letters, 2023)
Background: STAM-binding protein-like 1 (STAMBPL1) functions as a deubiquitinase to cleave Lys63 ubiquitin linkage, and is associated with cancer dissemination and progression. The role of STAMBPL1 in colorectal cancer (CRC) remains unclear.Methods: STAMBPL1 expression was determined by western blot and qRT-PCR. Cell proliferation was detected by colony formation and MTT assays, and apoptosis was assessed by flow cytometry. The metastasis was evaluated by transwell and wound healing assays. An animal xenograft experiment was used to investigate the effect of STAMBPL1 on tumor growth.Results: The expression of STAMBPL1 was elevated in CRC cells. Knockdown of STAMBPL1 reduced cell viability of CRC and suppressed the proliferation, invasion, and migration. Apoptosis of CRC was induced by silence of STAMBPL1. Tumor growth of CRC was also suppressed by the silence of STAMBPL1. Knockdown of STAMBPL1 increased IΚB and decreased phosphorylation of IΚB to reduce p65 phosphorylation.Conclusion: Knockdown of STAMBPL1 inhibited cell growth and metastasis of CRC through inactivation of the NF-ΚB pathway.
Keywords: tumor growth